Humoral Immunogenicity and Efficacy of a Single Dose of ChAdOx1 MERS Vaccine Candidate in Dromedary Camels - Alharbi, Naif Khalaf; Qasim, Ibrahim; Almasoud, Abdulrahman; Aljami, Haya A.; Alenazi, Mohamed W.; Alhafufi, Ali; Aldibasi, Omar S.; Hashem, Anwar M.; Kasem, Samy; Albrahim, Raed; Aldubaib, Musaad; Almansour, Ali; et al. (Scientific reports, 2019)
MERS-CoV seronegative and seropositive camels received a single intramuscular dose of ChAdOx1 MERS, a replication-deficient adenoviral vectored vaccine expressing MERS-CoV spike protein, with further groups receiving control vaccinations. Infectious camels with active naturally acquired MERS-CoV infection, were co-housed with the vaccinated camels at a ratio of 1:2 (infected:vaccinated); nasal discharge and virus titres were monitored for 14 days. Overall, the vaccination reduced virus shedding and nasal discharge (p = 0.0059 and p = 0.0274, respectively). Antibody responses in seropositive camels were enhancedby the vaccine; these camels had a higher average age than seronegative. Older seronegative camels responded more strongly to vaccination than younger animals; and neutralising antibodies were detected in nasal swabs. Further work is required to optimise vaccine regimens for younger seronegative camels.